1980
DOI: 10.1182/blood.v56.6.1150.1150
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of murine pluripotential stem cell proliferation in vivo by lithium carbonate

Abstract: The effect of administering lithium in vivo on murine pluripotential stem cell proliferation was studied. Lithium was injected i.p. at various meq/liter concentrations (0.5–5.0 meq/liter). Data was obtained establishing that lithium increased the pluripotential stem cell population from normal mice as measured by the Till and McCulloch CFUs assay. Significant increases were demonstrated in: (1) bone marrow CFUs; (2) bone marrow organ cellularity, and (3) peripheral blood WBC. Marrow CFUs increase was maximum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…Dealing with lithium poisoning, cytopenias are scarcely reported. Lithium can reduce erythroid progenitor growth in vitro [ 7 ]. On mice [ 8 ], lithium treatment with 20 mg/kg daily can reduce erythropoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…Dealing with lithium poisoning, cytopenias are scarcely reported. Lithium can reduce erythroid progenitor growth in vitro [ 7 ]. On mice [ 8 ], lithium treatment with 20 mg/kg daily can reduce erythropoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…Lithium carbonate does not injure the liver in the routine dose and is a perfect substitution for ATD. Study has found that an additive effect of increasing white blood cells was observed in patients treated with lithium carbonate because it may modulate granulocytopoiesis [ 20 ]. Moreover, lithium salts can not only increase the level of CD34 but also induce granulocyte colony-stimulating factor and increase the number of neutrophils by stimulating bone marrow; thus, it is a good choice in patients with leucopenia or agranulocytosis [ 21 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Li also acts on pluripotent stem cells, platelet production and megakaryocytes [71]. Li carbonate at a dose of 1milliequivalent per litre (mEq/l) of solution is shown to increase bone marrow CFUs and granulopoiesis [72]. PI3Kand mTOR signalling is regulated by GSK3.…”
Section: Lithium and Haematopoiesismentioning
confidence: 99%